Peran Bank Pembiayaan Rakyat Syariah (BPRS) Puduarta Insani dalam Pemberdayaan Ekonomi Masyarakat Melalui Pembiayaan UMKM - Alya Avina; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
This research aims to determine the role of the Puduarta Insani Sharia People's Financing Bank (BPRS) in developing Micro, Small and Medium Enterprises (MSMEs), as well as to find out what are the obstacles of Puduarta Insani Sharia People's Financing Bank (BPRS) in developing Micro Small and Medium Enterprises (MSMEs). This study uses a qualitative method with a descriptive approach, with primary and secondary data sources. The results of the research indicate that the role of the Puduarta Insani Sharia People's Financing Bank (BPRS) in terms of developing MSMEs in the people of North Sumatra is quite good. By providing financing to businesses that require additional capital to open or increase their business capacity. Constraints that occur in developing MSMEs, one of which is the role of Islamic banks as partners in the MSME sector which is considered unfinished, namely Islamic banks only help in terms of financing funds but have not participated in helping to advance MSMEs in increasing income.